2008
DOI: 10.1163/157181808x311231
|View full text |Cite
|
Sign up to set email alerts
|

Children's Participation and International Development: Attending to the Political

Abstract: Since the early 1990s participation has grown to become a key notion amongst child-focused international and intergovernmental development organisations. By means of participatory projects such bodies commonly seek to achieve transformation of children's lives. While considerable consideration has been given to the technical, institutional and attitudinal challenges to achievement of this goal, far less attention has been paid to the political context in which such transformation is sought. Drawing upon the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
203
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(219 citation statements)
references
References 0 publications
2
203
0
14
Order By: Relevance
“…Hart (2008) notes at least three answers: transformation for those involved, such as extending skills, experiences and networks of children and young people, and changed relationships between children, young people and adults; transformation as a product of these activities, for example influencing a particular decision; and broad societal transformation due to the accumulated combination of the first two. While the first is well evidenced, transformations of the second and third types are less well so.…”
Section: Resultsmentioning
confidence: 99%
“…Hart (2008) notes at least three answers: transformation for those involved, such as extending skills, experiences and networks of children and young people, and changed relationships between children, young people and adults; transformation as a product of these activities, for example influencing a particular decision; and broad societal transformation due to the accumulated combination of the first two. While the first is well evidenced, transformations of the second and third types are less well so.…”
Section: Resultsmentioning
confidence: 99%
“…When we analysed qualitative interview responses about child welfare workers' views of children's participation using Hart's () ladder of participation, we found that approximately one out of four workers conceptualized children's participation as non‐participation : children were not considered decision‐makers; rather, these workers' perceptions corresponded to the themes manipulation, decoration and tokenism as understood by Hart. This type of participation is window dressing and cannot be considered participation as conceptualized in Article 12 of the UNCRC.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we are returning to the historical underpinnings of individual rights, which emphasized individuals' sovereignty or authority over their own lives (Hunt ), to emphasize that the concept of rights is inextricably linked to the concept of power; even though Article 12 does not explicitly mention children's decision‐making power, the idea of giving a child's opinion ‘due weight’ is related to the level of a child's authority, sovereignty and ultimately, power. Based on the assumption that rights and power (to make decisions) are intertwined concepts, we found Hart's () ladder of children's participation a useful index to examine child welfare workers' perceptions of children's participation. Hart's ladder, shown in Fig.…”
Section: Legal Platform and Conceptual Frameworkmentioning
confidence: 99%
“…Will we have a working vocabulary that accommodates 'child worker', 'child citizen', or 'child politician' as easily as 'child soldier'? Will the term 'child-soldier' become sufficiently unprofitable that it can be replaced by CAFF (Children Affected by Fighting Forces) and therefore permanently foreclose the lumping together of child soldier attributes (Hart 2008)? Will 'minor politics' rescue children 'from the depoliticized territory of the private sphere of the family, or the technical sphere of service delivery' (Dahlberg and Moss 2005, 154)?…”
Section: Back To the Futurementioning
confidence: 99%